Characteristics of Neonatal Hyperbilirubinemia at West Javaâs Top Referral Hospital, Indonesia. - Yahya, Nurain; Yuniati, Tetty; Lubis, Leonardo (Althea Medical Journal, 2017)
Background: Neonatal hyperbilirubinemia or neonatal jaundice is a common disorder and considered as one of the main problems in neonatal period worldwide with high incidence, especially in Asia and Southeast Asia region. This study was conducted to determine the characteristics of neonatal hyperbilirubinemia including the prevalence and frequency of neonatal hyperbilirubinemia causes at Dr. Hasan Sadikin General Hospital in 2012.Methods: This descriptive study was conducted at Dr. Hasan Sadikin General Hospital using the cross-sectional method. Four hundred and twenty five cases of neonatal hyperbilirubinemia in hospitalized and outpatients, from 1 January to 31 December 2012 were included in this descriptive study.Results: The prevalence of neonatal hyperbilirubinemia was about 4.08%. Causes were identified in 95 cases and the most common cause of neonatal hyperbilirubinemia during this period of time was physiological causes (23.2%). Other causes included neonatal hepatitis (14.7%), other hemolytic causes (13.7%), infection (12.6%), ABO incompatibility (11.6%) and breastfeeding (11.6%).Conclusions: Neonatal hyperbilirubinemia cases are common and remain as one of the neonatal problems in Dr. Hasan Sadikin General Hospital, thus prevention and proper management of neonatal hyperbilirubinemia should be implemented.Â DOI:Â 10.15850/amj.v4n2.1065